Apache Hadoop YARN LiveLessons (sneak peek video training) - Murthy, Arun.; Eadline, Doug.; Vavilapalli, Vinod; Safari eBooks ([Indianapolis, Ind.?] : Addison-Wesley Professional, 2013)
"Apache Hadoop YARN Fundamentals LiveLessons is the first complete video training course on the basics of Apache Hadoop version 2 with YARN. The tutorial begins with MapReduce and Big Data fundamentals and moves to YARN design, installation (laptop, cluster, and cloud) , administration, running applications (MapReduce2, Pig and Hive), writing new applications, and useful frameworks. Additional coverage of Ambari, Ganglia, Nagios and the Hortonworks HDP is provided."--Resource description page.
Presenter, Doug Eadline.
Title from resource description page (viewed Feb. 5, 2014).
Keywords: Apache Hadoop; Electronic data processing -- Distributed processing; Electronic books